IDENTIFIKASI FAKTOR KESULITAN SISWA DALAM MEWUJUDKAN PERILAKU SEMANGAT KEBANGSAAN DALAM KEHIDUPAN PADA BIDANG STUDY PKN DI SMA SWASTA CERDAS BANGSA DELITUA TAHUN 2021 - Datten Datten; Endalina Br Karo Sekali (Universitas Quality, 2022)
This study aims to determine the students' abilities and the factors that cause students' learning difficulties in materializing the behavior of the national spirit in life in the field of Civics study in class XI of SMA Swasta Cerdas Bangsa for the Academic Year 2020/2021. This research was conducted at SMA Swasta Cerdas Bangsa with a sample of 32 students from SMA class XI IPA. This type of research is descriptive quantitative research. The data collection instruments used are, questionnaires and tests. After analyzing the data on the results of the study, it was found that the students' ability to materialize the behavior of the national spirit in life in the Civics study field, obtained an average score of 71.11 and the criteria were quite capable. The results showed that the factors causing learning difficulties for Class XI IPA students of SMA Swasta Cerdas Bangsa for the Academic Year 2020/2021 in the Civics Study on Materials Realizing the behavior of the national spirit in life was an internal factor from the students themselves, namely the lack of ability to understand the material given by the teacher. by online. External factors are also the cause of student learning difficulties, namely the lack of learning facilities available to students, lack of attention from parents in the online learning system that is being implemented in the world of education.